House helping an alternative profession - Apura, Therese Dawn D.; Areño, Faye Joy Y.; Judicpa, Alen A.; Pabiona, Mark Anthony P. (2002.)
We cannot deny that fact that most Filipinos live in poverty brought about by unemployment, lack of formal education, and most especially by the economic crisis in the Philippines, and similarly the rest of the world, is facing. Jobs are increasingly difficult to find. Most Filipinos, especially in the rural areas, cannot afford to have any formal education. If they can, all they can come up with is elementary or high school. Worst, the Philippines, still, is not progressing economically. Due to these problems Filipinos tend to take any job thay can find to earn a living. Young and old, male or female, educated or not, would work for anything they could find just to support themselves and their families. Having these circumstances, employment within a household seems to be an attractive occupation. In a set-up wherein husband and wife both work for the family, househelpers seems to be the only solution to do the household chores. With the demand for househelpers, its appears to be the easiest job around. The popularity and the increasing demand for househelpers led the researchers to ask whether it is possible to elevate the house-helping job into a profession comparable in some degree to other professions. The perception whether or not house helping is a profession will determine the manner by which househelpers are treated nowadays. The kind of insight the researchers would like to know is from the househelpers themselves as well as from their employers. These considerations thus led to the study "Househelping : An Aternative Profession". This study aims to determine whether or not househelping could indeed be elevated to a profession. Specifically, it aims to evaluate the significance of having househelpers, to determine the criteria in considering a certain job a profession, and to obtain knowledge of how househelpers and their employers consider househelping as a job. The respondents in this study are composed of random samples of househelpers and their employers in Iloilo City. The study was conducted from January to March 2002 and used a descriptive method of research. Questionnaires were used to gather data. The results of the survey were analyzed using the Chi-square test or the goodness-of-fit test. The findings of the study shows that majority of the househelpers is in the high school level and earns only as much as P1,000 to P3,000 per month. The employers and the househelpers considered that househelping can be a profession. And the minimum requirements needed are experience, training and pleasing personality.
Research Paper (BA 200 - Business Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 2002..